Pengaruh Model Problem Based Learning Dengan Pendekatan Deep Learning Berbasis Noken Terhadap Hasil Belajar Peserta Didik - Asiroha Siboro; Kaleb Amaghi Yenusi; Sri Rosepda Sebayang; Mujasam Mujasam; Berliana Anggun Dwicahyani; Fadillah Ramadhani (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) model with a deep learning approach based on local wisdom (noken) on students’ learning outcomes. This research is motivated by the low level of learning outcomes caused by memorization-oriented and less contextual learning processes. The method used was a quasi-experimental design with a pretest-posttest control group. The subjects of this study were students divided into experimental and control groups. The research instrument was a learning outcome test that had been validated and tested for reliability. Data were collected through pretest and posttest and analyzed using an independent t-test. The results showed that the mean score of the experimental group was 81.45, which was higher than that of the control group (73.34). The t-test result indicated that t-count = 3.42 > t-table = 2.00 with a significance value of 0.002 < 0.05, indicating a significant effect. Therefore, it can be concluded that the PBL model with a deep learning approach based on noken is effective in improving students’ learning outcomes.